A heap of sound symbolism - Staps, Camil (Nordlyd, 2026)
Classifiers like drop or splash (of water) are commonly taken to denote portions of an approximate quantity in a specific shape. But if this is so, why can we not talk about a #drop of wood, even though wood can, in principle, occur in the size and shape of a drop? Rooryck (2024) argues that static properties like size and shape are secondary, and that classifiers primarily express what kind of transformations materials undergo under the influence of a force. Thus, wood cannot undergo the event in which a drop is created. This paper presents evidence from sound symbolism for this emphasis on dynamic properties. Although some sounds in classifiers appear to be motivated by static properties (e.g., the labial /p/ in drop by its round shape), sound symbolism motivated by dynamic properties is more pervasive: a splash is formed in an event in which a portion of liquid moves through the air (/s/), followed by impact on a surface (/p/), radial dispersion of smaller blobs of liquid (/l/), and the impacts of these smaller blobs shortly after one another (/ʃ/). This calls for a more refined view on the semantics of classifiers.